Opportunities and Challenges for Improving the Productivity of Swamp Buffaloes in Southeastern Asia - Pineda, Paulene S.; Flores, Ester B.; Herrera, Jesus Rommel V.; Low, Wai Yee (Frontiers in Genetics, 2021)
The swamp buffalo is a domesticated animal commonly found in Southeast Asia. It is a highly valued agricultural animal for smallholders, but the production of this species has unfortunately declined in the last decades due to rising farm mechanization. While swamp buffalo still plays a role in farmland cultivation, the prospect of this species has shifted from draft power to meat, milk and hide production. The current status of swamp buffaloes in Southeast Asia are still understudied in comparison to its counterparts such as the riverine buffaloes and cattle. This review discusses the background of swamp buffalo, with an emphasis on recent work on this species in Southeast Asia, and associated genetics and genomics work such as cytogenetic studies, phylogeny, domestication and migration, and genetic sequences. Recent challenges to realize the potential of this species in the agriculture industry are also discussed. Limited genetic resources for swamp buffalo has called for more genomics work to be done on this species including decoding its genome. As the economy progresses and farm mechanization is trending, research and development for swamp buffaloes is focused on enhancing its productivity on agriculturally important traits using genomic selection. The use of genomic markers is a powerful tool to efficiently utilize the potential of this animal for food security and animal conservation. Understanding its genetic and retaining and maximizing its adaptability to harsher environments is a strategic move for food security in poorer nations in Southeast Asia in the face of climate change.